The Optimal Portfolio of Start-Up Firms in Venture Capital Finance - Vesa Kanniainen; Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2000)
A venture capitalist faces a trade-off between the extent of managerial advice allocated to each start-up and the total number of firms advised. Diminishing returns to advice per firm call for a larger portfolio. As advice gets diluted, further expansion of the portfolio eventually becomes unprofitable.
Keywords: 330; Venture capital finance; double-sided moral hazard; company portfolio